Strategic Transformation Toward World-Class University: The Quacquarelli Symonds (QS) Ranking System Implementation at a Public University in South Kalimantan - Mutiani Mutiani; Rifiana Rifiana; Nurmelati Septiana; Rizky Amelia; Fadloe Robby (Program Studi Pendidikan IPS, 2026)
The global higher education landscape demands universities to continuously enhance their competitiveness through systematic quality improvement and international recognition. A regional Indonesian university (hereinafter referred to as